Case report: Huppke–Brendel syndrome in an adult, mistaken for and treated as Wilson disease for 25 years - Kirk, Frederik Teicher; Munk, Ditte Emilie; Ek, Jakob; Birk Møller, Lisbeth; Bendixen Thorup, Mette; Hvid Danielsen, Erik; Vilstrup, Hendrik; Ott, Peter; Damgaard Sandahl, Thomas (Frontiers in Neurology, 2022)
Background Huppke-Brendel (HB) syndrome is an autosomal recessive disease caused by variants in the SLC33A1 gene. Since 2012, less than ten patients have been reported, none survived year six. With neurologic involvement and ceruloplasmin deficiency, it may mimic Wilson disease. Objectives and Methods We report the first adult patient with HB. Results The patient suffered from moderate intellectual disability, partial hearing loss, spastic ataxia, hypotonia and unilateral tremor of parkinsonian type. At age 29 she was diagnosed with Wilson disease based on neurology, elevated 24H urinary copper, low ceruloplasmin, and pathological 65Cu test. 25 years later, genetic testing did not support Wilson disease or aceruloplasminemia. Full genome sequencing revealed two likely pathogenic variants in SLC33A1 which combined with reevaluation of neurologic symptoms and MRI suggested the diagnosis of HB. Conclusion Adult patients with HB exist and may be confused with Wilson disease. Low ceruloplasmin and absence of ATP7B variants should raise suspicion.